ANALISIS INTENSITAS DAN ELASTISITAS FAKTOR PRODUKSI INDUSTRI UKIRAN KAYU DI KOTA PALEMBANG - Azwardi Azwardi; Yuliansyah M. Diah (Department of Development Economics, Universitas Sriwijaya, 2006)
This research is purposed to know the elasticity and intencity of production function and eficiency of the wood engraving industry in Palembang. By using CES production function we can knowÂ the wood engraving industry is more capital intensive and the substitution elasticity is inelatis. And then, based on the production scale we can know that the wood engraving industry is constant return to scale. Keywords: elasticity, intencity, production, eficiciency, industry